THE BÍLINA TUNNEL – SELECTED GEOTECHNICAL ASPECTS OF A PROPOSED UNDERGROUND STRUCTURE - Viktor Sotorník; Petr Černoch; Jiří Košťál (Acta Polytechnica CTU Proceedings, 2022)
Every workday the city of Bílina, with the I/13 road running through it, suffers from traffic congestion. The road is designed as dual carriageway outside Bílina but only as a single carriageway inside the city. Three roundabouts further complicate the situation. As a solution a 1,3 km long tunnel going under the city was proposed. The preliminary geotechnical investigation describes the geological conditions of the area, suggests the most appropriate localisation details of the tunnel, points out several complications that can be expected and finally offers solutions to mitigate them.